Referring the heads of administrative units to retirement and its implications (Journal of Imam Al-Kadhim College, 2023)
Abstract The relationship between the employee and the administration is not permanent and does not end with the death of the public employee. On the contrary, the functional bond expires in many ways, including the employee's cessation of holding the public position when he reaches a certain age, or when his services acceptable for retirement reach a certain limit and may end. The employee’s service ends with the expiry of a limited period that usually does not exceed forty years, and there is nothing strange about that, and everything is timed for it. The most important of which is his right to salary. Returning to the amended Law No. 35 of 2003 of the governorates that are not organized in the region, we find that he set a rule that contradicts the general rule, and devised a retirement referral system for the elected heads and members of local councils those whose years of service in the position or the council do not exceed four years, if the law stipulates that members of the councils, heads of administrative units and deputy governors who occupy their positions under the provisions of this law shall be entitled to a retirement salary of not less than 80% of the remuneration they receive under this law after the end of the term elections, or if he suffers from a disability that impedes him from performing his job duties.
Keywords: Heads of administrative units, the retirement, Referral